Synergistic Effect of Betaines and Dialkyl Chain Anionic Surfactants on Interfacial Arrangement A Molecular Dynamics Simulation Study - Liu, Mengxin (Langmuir : the ACS journal of surfaces and colloids, 2024)
Mixed systems of betaines and anionic surfactants can have a significant synergistic effect and greatly reduce the interfacial tension (IFT), which has attracted an extensive amount of attention. However, this synergistic effect requires an anionic surfactant and betaine molecular size matching, which limits the scope of its application. In this work, we studied three mixed systems of sodium dialkyl sulfosuccinate (AOT) and betaines with different sizes by molecular dynamics simulation and an IFT experiment and explored the interfacial behavior and synergistic mechanism of AOT in single and mixed systems. The hydrophobic tail chain center angle, average rising height of carbon atoms, stretch degree and distance between the terminal carbon atoms of AOT, and tilt angles of betaine were calculated and analyzed in detail. Simulation results showed that the hydrophobic tail chain center angle of AOT in the single system was smaller, and it tended to extend into the oil phase. After being mixed with different betaines, AOT can adjust its size according to the interfacial vacancies of different betaine systems by changing the alkyl chain orientation and forming tighter interfacial films. The IFT experiment showed that betaine/AOT mixed systems achieved a lower IFT value compared with that of the single system, indicating that AOT showed a synergistic effect with betaines with different structures. This study will be importantly instructively significant for the design and research of betaine mixed systems in crude oil exploitation